Current state of quality of life and patient-reported outcomes research. (November 2019) - Bottomley, Andrew; Reijneveld, Jaap C.; Koller, Michael; Flechtner, Henning; Tomaszewski, Krzysztof A.; Greimel, Eva; ,
Abstract: The 5th EORTC Quality of Life in Cancer Clinical Trials Conference presented the current state of quality of life and other patient-reported outcomes (PROs) research from the perspectives of researchers, regulators, industry representatives, patients and patient advocates and health care professionals. A major theme was the assessment of the burden of cancer treatments, and this was discussed in terms of regulatory challenges in using PRO assessments in clinical trials, patients' experiences in cancer clinical trials, innovative methods and standardisation in cancer research, innovative methods across the disease sites or populations and cancer survivorship. Conferees demonstrated that PROs are becoming more accepted and major efforts are ongoing internationally to standardise PROs measurement, analysis and reporting in trials. Regulators are keen to collaborate with all stakeholders to ensure that the right questions are asked and the right answers are communicated. Improved technology and increased flexibility of measurement instruments are making PROs data more robust. Patients are being encouraged to be patient partners. International collaborations are essential, because this work cannot be accomplished on a national level. Highlights: Patient-reported outcomes (PROs) are now well accepted and international efforts are aiming to standardise PRO's in trials. Regulators are keen to collaborate with all stakeholders to ensure the correct PRO questions are being addressed. Improved technology and increased flexibility of quality of life instruments are making PRO data more robust. The patient voice is strong and patients are being encouraged to be true patient partners. International collaborations are essential, given the globalisation of clinical research.